Penerapan Model Rapid Application Development (RAD) Dalam Rancang Bangun Sistem Informasi Warga - Ade Suryanto; M. Ibnu Maliki (Infotek: Jurnal Informatika dan Teknologi, 2022)
At this time the advancement of technology is so very fast. Almost all sectors of life take advantage of these technological advances. From the fields of economy, education, to the field of government, there is no exception for lower-level government services, namely the Rukun Tetangga who can also take advantage of this technological advancement in their services. In the neighborhood of RT 007, the services provided are still manual, for this reason, a design for the creation of a citizen information system that helps in the service process will be carried out. Making this website application uses the Rapid Application Development method in its development and this application is also built using the Codeigniter 3 framework and website-based Bootstrap. To build this system the programming languages used are HTML, PHP, JAVASCRIPT and CSS. This website application that was built aims to make it easier for residents to submit cover letters, make it easier to share RT cash financial information, and also make it easier for Leader RT to make reports. Tests carried out by this application use Black Box Testing which is centered on the input process or input only.